Identification of anticancer drugs to radiosensitise BRAFwild-type and mutant colorectal cancer - Carter, R; Cheraghchi-Bashi, A; Westhorpe, A; Yu, S; Shanneik, Y; Seraia, E; Ouaret, D; Inoue, Y; Koch, C; Wilding, J; Ebner, D; Ryan, A; et al. (China Anti-Cancer Association, 2019)
Objective: Patients with BRAF-mutant colorectal cancer (CRC) have a poor prognosis. Molecular status is not currently used to select which drug to use in combination with radiotherapy. Our aim was to identify drugs that radiosensitise CRC cells with known BRAF status. Methods: We screened 298 oncological drugs with and without ionising radiation in colorectal cancer cells isogenic for BRAF. Hits from rank product analysis were validated in a 16-cell line panel of human CRC cell lines, using clonogenic survival assays and xenograft models in vivo. Results: Most consistently identified hits were drugs targeting cell growth/proliferation or DNA damage repair. The most effective class of drugs that radiosensitised wild-type and mutant cell lines was PARP inhibitors. In clonogenic survival assays, talazoparib produced a radiation enhancement ratio of 1.9 in DLD1 (BRAF-wildtype) cells and 1.8 in RKO (BRAF V600E) cells. In DLD1 xenografts, talazoparib significantly increased the inhibitory effect of radiation on tumour growth (P ≤ 0.01). Conclusions: Our method for screening large drug libraries for radiosensitisation has identified PARP inhibitors as promising radiosensitisers of colorectal cancer cells with wild-type and mutant BRAF backgrounds.